An inducible potato (E, E)‐farnesol synthase confers tolerance against bacterial pathogens in potato and tobacco. (12th July 2022) - Dwivedi, Varun; Kumar, Sarma Rajeev; Shilpashree, H. B.; Krishna, Ram; Rao, Srinivas; Shasany, Ajit K.; Olsson, Shannon B.; Nagegowda, Dinesh A.
SUMMARY: Terpene synthases (TPSs) have diverse biological functions in plants. Though the roles of TPSs in herbivore defense are well established in many plant species, their role in bacterial defense has been scarce and is emerging. Through functional genomics, here we report the in planta role of potato ( Solanum tuberosum ) terpene synthase (StTPS18) in bacterial defense. Expression of StTPS18 was highest in leaves and was induced in response to Pseudomonas syringae and methyl jasmonate treatments. The recombinant StTPS18 exhibited bona fide ( E, E )‐farnesol synthase activity forming a sesquiterpenoid, ( E, E )‐farnesol as the sole product, utilising ( E, E )‐farnesyl diphosphate (FPP). Subcellular localization of GFP fusion protein revealed that StTPS18 is localized to the cytosol. Silencing and overexpression of StTPS18 in potato resulted in reduced and enhanced tolerance, respectively, to bacterial pathogens P. syringae and Ralstonia solanacearum . Bacterial growth assay using medium containing ( E, E )‐farnesol significantly inhibited P. syringae growth. Moreover, StTPS18 overexpressing transgenic potato and Nicotiana tabacum leaves, and ( E, E )‐farnesol and P. syringae infiltrated potato leaves exhibited elevated expression of sterol pathway and members of pathogenesis‐related genes with enhanced phytosterol accumulation. Interestingly, enhanced phytosterols in 13 C3 ‐( E, E )‐farnesol infiltrated potato leaves were devoid of any noticeable 13 C labeling, indicating no direct utilization of ( E, E )‐farnesol in phytosterols formation. Furthermore, leaves of StTPS18 overexpressing transgenic lines had no detectable ( E, E )‐farnesol similar to the control plant, and emitted lower levels of sesquiterpenes than the control. These findings point towards an indirect involvement of StTPS18 and its product ( E, E )‐farnesol in bacterial defense through upregulation of phytosterol biosynthesis and defense genes. Significance Statement: Here we show that a pathogen‐responsive potato sesquiterpene synthase forming ( E, E )‐farnesol confers indirect defense against bacterial pathogens through induced phytosterol biosynthesis and defense response in potato and tobacco. The findings demonstrate an indirect role of ( E, E )‐farnesol in plant biotic stress tolerance.